2020
DOI: 10.18517/ijaseit.10.4.10237
|View full text |Cite
|
Sign up to set email alerts
|

Categorization of Malay Social Media Text and Normalization of Spelling Variations and Vowel-less Words

Abstract: As more data are being introduced, it brings along with it missing values, inconsistencies, and heterogeneities, or so-called unclean aspects. Text analytics relies on clean data to produce reliable results. Pre-processing is an essential phase in text analytics, specifically language detection and normalization. The problem with conducting text analytics on Malay social media text is how substantially it has transformed from formal Malay in terms of spelling and construction, making it difficult to process th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…In Nigeria, use of social media had a negative effect on college students' spelling ability and the conventional way of writing in examinations and letters (Wilson, 2018). In Malaysia, some of the weaknesses found in Malay social media texts were spelling variations, and vowel-less words (Maskat & Rahman, 2020). Use of pairs of word forms covering seven types of spelling variation in English was found on Twitter and Reddit (Nguyen, Grieve, Scott, Bel & Zong, 2020).…”
Section: The Spelling Error Distribution and Gravitymentioning
confidence: 99%
See 1 more Smart Citation
“…In Nigeria, use of social media had a negative effect on college students' spelling ability and the conventional way of writing in examinations and letters (Wilson, 2018). In Malaysia, some of the weaknesses found in Malay social media texts were spelling variations, and vowel-less words (Maskat & Rahman, 2020). Use of pairs of word forms covering seven types of spelling variation in English was found on Twitter and Reddit (Nguyen, Grieve, Scott, Bel & Zong, 2020).…”
Section: The Spelling Error Distribution and Gravitymentioning
confidence: 99%
“…The researcher found that use of social media had a negative effect on college students' spelling ability and the conventional way of writing especially in examinations and letters. Some of the weaknesses found in Malay social media texts were spelling variations, and vowel-less words, Malay-English mix in sentences, loan words/phrases, and slang-based words (Maskat & Rahman, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Grasping user perspectives assumes a pivotal role in fostering precise sentiment analysis within the context of social media slang analytics, as it facilitates the interpretation of subtle slang expressions and their associated connotations in online interactions. Additionally, numerous studies have predominantly focused on widely recognized social media platforms such as Twitter [7] [12] [13]. However, an extensive assessment of the diversity encompassing platforms and data sources employed in slang analytics is conspicuously absent.…”
Section: Introductionmentioning
confidence: 99%